2023
DOI: 10.1002/sstr.202200387
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Organic Frameworks with Molecular Electronic Modulation as Metal‐Free Electrocatalysts for Efficient Hydrogen Peroxide Production

Abstract: Tuning the electronic property of active center to balance the adsorption ability and reactivity of oxygen is essential for achieving 2e− oxygen reduction reaction (ORR) for electrocatalytic synthesis of hydrogen peroxide (H2O2), still represents a grand challenge. Herein, different by‐design building blocks are introduced to regulate the electronic structure of catalytically active centers in covalent organic frameworks (COFs). Theoretical calculation reveals that adsorption ability of oxygen molecule (O2) ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Thus, we emphasize that much more research should be devoted to both the design of COF-based photocatalysts and the engineering strategy of H 2 O 2 synthesis to achieve the goal. Surprisingly, only a few COFs have been identified as electrocatalysts for H 2 O 2 production. However, the investigation of COF-based materials for photo­(electro)­catalytic H 2 O 2 production has not been explored yet, which may be an promising strategy in the near future. Thus, future research should focus on the exploration of more organic linkers that could facilitate the generation of H 2 O 2 from oxygen by photo­(electro)­catalysis via the oxygen reduction reaction pathway.…”
Section: Photocatalytic Experimental Methods and Measurement Of Hydro...mentioning
confidence: 99%
“…Thus, we emphasize that much more research should be devoted to both the design of COF-based photocatalysts and the engineering strategy of H 2 O 2 synthesis to achieve the goal. Surprisingly, only a few COFs have been identified as electrocatalysts for H 2 O 2 production. However, the investigation of COF-based materials for photo­(electro)­catalytic H 2 O 2 production has not been explored yet, which may be an promising strategy in the near future. Thus, future research should focus on the exploration of more organic linkers that could facilitate the generation of H 2 O 2 from oxygen by photo­(electro)­catalysis via the oxygen reduction reaction pathway.…”
Section: Photocatalytic Experimental Methods and Measurement Of Hydro...mentioning
confidence: 99%
“…Density functional theory 71 calculations further revealed that the deliberate combination of COF-42 with Ti 3 C 2 T x provides a more diverse array of active positions with appropriate DG H values, resulting in an enhanced hydrogen generation rate. 85 In another study Wang et al prepared well connected 2D/2D hybrid by coupling of MXene with CoBDC nanosheets by a facile in situ grown approach. The as synthesized CoBDC/MXene catalyst showed lower over potential values of 29, 41 and 76 mV in alkaline, acidic and neutral environment respectively.…”
Section: Mxene-based Hybrid Architectures For Hermentioning
confidence: 99%
“…It should be noted that most of the COF-based photocatalysts reported thus far are based on imine linkages and recent studies have demonstrated that the construction of suitable linkages or linkage tailoring could also significantly affect the performance of the corresponding COFs. 59,60 As an example, the group of Thomas reported four chemically stable quinoline-4-carboxylic acid DMCR-COFs via the one-pot Doebner reaction for photocatalytic H 2 O 2 production, while the corresponding imine-based COF (imine-1) was also synthesized to compare its performance with those of DMCR-COFs (Fig. 11a).…”
Section: Linkage Tailoringmentioning
confidence: 99%